2022
DOI: 10.3847/1538-4357/ac4bbe
|View full text |Cite
|
Sign up to set email alerts
|

B-fields in Star-forming Region Observations (BISTRO): Magnetic Fields in the Filamentary Structures of Serpens Main

Abstract: We present 850 μm polarimetric observations toward the Serpens Main molecular cloud obtained using the POL-2 polarimeter on the James Clerk Maxwell Telescope as part of the B-fields In STar-forming Region Observations survey. These observations probe the magnetic field morphology of the Serpens Main molecular cloud on about 6000 au scales, which consists of cores and six filaments with different physical properties such as density and star formation activity. Using the histogram of relative orientation (HRO) t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…Li et al (2022) compared the inferred magnetic field from HAWC+ with the Herschel column density map in Taurus/B211 and found that the magnetic field is more likely perpendicular to the column density structures in B211. Kwon et al (2022) found negative ξ values in the Serpens Main cloud with JCMT observations at a resolution of 14′′ (~0.03 pc), where they suggested that the first column density bin at N H_{2} ~9.3 × 10 21 cm −2 is approximately the transition column density. In Kwon et al (2022), the ξ decreases from 0 to negative values from N H_{2} ~9.3 × 10 21 cm −2 to ~4.6 × 10 22 cm −2 , which mainly corresponds 9 A significant amount of the diffuse ISM is in the atomic phase, while molecular clouds are in the molecular phase.…”
Section: Observationsmentioning
confidence: 84%
“…Li et al (2022) compared the inferred magnetic field from HAWC+ with the Herschel column density map in Taurus/B211 and found that the magnetic field is more likely perpendicular to the column density structures in B211. Kwon et al (2022) found negative ξ values in the Serpens Main cloud with JCMT observations at a resolution of 14′′ (~0.03 pc), where they suggested that the first column density bin at N H_{2} ~9.3 × 10 21 cm −2 is approximately the transition column density. In Kwon et al (2022), the ξ decreases from 0 to negative values from N H_{2} ~9.3 × 10 21 cm −2 to ~4.6 × 10 22 cm −2 , which mainly corresponds 9 A significant amount of the diffuse ISM is in the atomic phase, while molecular clouds are in the molecular phase.…”
Section: Observationsmentioning
confidence: 84%
“…Kwon et al found negative ξ values in the Serpens Main cloud with JCMT observations at a resolution of 14 ′′ (∼0.03 pc), where they suggested that the first column density bin at N H 2 ∼ 9.3 × 10 21 cm −2 is approximately the transition column density. In Kwon et al (2022), the ξ decreases from 0 to negative values from N H 2 ∼ 9.3 × 10 21 cm −2 to ∼ 4.6 × 10 22 cm −2 , which mainly corresponds to the filamentary structures. Between N H 2 ∼ 4.6 × 10 22 cm −2 to ∼ 10 23 cm −2 , ξ increases back to 0, suggesting that the magnetic fields are trending parallel to elongated structures.…”
Section: Observationsmentioning
confidence: 93%
“…Numerous observatories, including the James Clark Maxwell Telescope (JCMT; e.g., Eswaraiah et al, 2021;Ngoc et al, 2021;Hwang et al, 2021;Kwon et al, 2022), Planck Space Observatory (e.g., Planck Collaboration et al, 2016;Alina et al, 2019), Atacama Large Millimeter/sub-millimeter Array (ALMA; e.g., Pattle et al, 2021;Cortés et al, 2021), Sub-Millimeter Array (SMA; e.g., Zhang et al, 2014), and Stratospheric Observatory for Infrared Astronomy (SOFIA; e.g., Chuss et al, 2019) have observed B POS of numerous star-forming regions. However, the number of B LOS observations of molecular clouds are still limited.…”
Section: D Magnetic Fieldsmentioning
confidence: 99%